Răspuns :
[tex]( \frac{1-3}{3}) ^{7} ÷ \frac{6 ^{5} }{9 ^{5} } [/tex]
[tex] (-\frac{2}{3}) * \frac{9 ^{5} }{6 ^{5} } [/tex]
[tex]-( \frac{2}{3}) * \frac{3 ^{10} }{(2*3) ^{5} } [/tex]
[tex] -\frac{2 ^{7} }{3 ^{7} } * \frac{3 ^{10} }{2 ^{5 } 3 ^{5} } [/tex]
[tex] (-\frac{2}{3}) * \frac{9 ^{5} }{6 ^{5} } [/tex]
[tex]-( \frac{2}{3}) * \frac{3 ^{10} }{(2*3) ^{5} } [/tex]
[tex] -\frac{2 ^{7} }{3 ^{7} } * \frac{3 ^{10} }{2 ^{5 } 3 ^{5} } [/tex]
= (-2/3)^7 : (6/9)^5 =
- 2^7 x 3^-7 x (3^2)^5 x 2^-5 x 3^-5 =
- 2^(7-5) x 3^(-7+10-5) =
- 2^2 x3^-2 = - 4/9
------------------------------
Succes in continuare!
------------------------------
- 2^7 x 3^-7 x (3^2)^5 x 2^-5 x 3^-5 =
- 2^(7-5) x 3^(-7+10-5) =
- 2^2 x3^-2 = - 4/9
------------------------------
Succes in continuare!
------------------------------